The effect of different motor constants to an commercial propeller. Issue 1 (July 2020) - Wahid, M Ab; Asmi, A N; Othman, N; Ardani, M I; Zain, M Z Md; Mansor, S
Abstract: This paper discussed the performance of a propeller with different motor constants such as the speed constants and motor resistance. The performance that was compared are the thrust, torque and total efficiency. There are many motors developed by the manufacturer, but the datasheet given are not complete and lack the information such as rotational speed and torque. This information is useful for designers and hobbyists to size their UAV or multicopter. In the market, there are many types of motors that make it difficult to choose the best motor. This research will perform analysis from the datasheet obtained from the manufacturer to see the effects of different motors to the propeller performance. It was gathered that for lower Kv such as KV980, it is better when higher torque than thrust is required. But for motor with speed constant above 1250 to 1400, the choice of motor will not have significant effect on the propeller performance. However, when size increase with higher Kv (more than 1400) the efficiency will drop.